Best Practices or Advertising Hype? A Content Analysis of Cosmetic Surgery Websites' Procedural, Risk, and Benefit Information. Issue 2 (3rd July 2017) - Goodman, J. Robyn
ABSTRACT: Little is known about the procedural, risk, and benefit information on cosmetic surgery websites despite cosmetic surgery's potential health risks and the facts that websites influence patient decisions to have surgery yet are advertising tools for the industry, and the majority of patients get their information from the Internet. This study content analyzed website information for the top five surgical procedures, finding few differences among procedure types and the procedure, risk, benefit, and candidate screening information. However, when differences were found, the least risky procedures provided more procedural information than the riskiest procedures. Approximately half of the sites mentioned no benefits and candidate screening, while half had a moderate to high amount of risk information. Thus, websites did emphasize risks over benefits. Moreover, few differences were found based on the site sponsor and risk, benefit, and procedure information. When differences were found, most showed commercial sites providing the greatest amount of information. Finally, this study concludes by discussing and presenting ethical guidelines for future cosmetic surgery advertising.